Baseline Sensitivity of Botryosphaeria spp. Isolated from Apples to Pyraclostrobin in Korea - Gwang-Jae Lim; Hae-Dam Kim; Jun-Woo Choi; Young Ju Nam; Ha-Kyoung Lee; Seung-Yeol Lee; Hee-Young Jung (The Plant Pathology Journal)
The genus Botryosphaeria cause white rot disease on apple trees, and control of this pathogens were primary relied on the fungicide applications. To investigate the pyraclostrobin sensitivity of Botryosphaeria spp. in Korea, 329 isolates were collected from eight regions between 2005 and 2023. Phylogenetic analysis based on the concatenated sequences of internal transcribed spacer, tef1, and tub2 revealed B. sinensis (287 out of 329 isolates) and B. kuwatsukai (42 out of 329 isolates). EC50 values of isolates ranged from 0.01 to 34.16 μg/ml (average, 3.03 μg/ml). Mean EC50 values and frequency distributions were similar among isolate groups, indicating no significant differences in sensitivity. Twenty less-sensitive and 20 sensitive isolates were selected and their cytochrome b (cyt b) genes analyzed, revealing no mutations in codons 129, 137, and 143. Whole gene sequencing revealed three distinct cyt b gene structures among Botryosphaeria spp., and all strains, including those with different EC50 values and species, showed consistent amino acid sequences. Furthermore, control efficacy on pyraclostrobin-treated apple fruits indicated no significant differences between the five least sensitive and five most sensitive isolates. These results provide the baseline sensitivity of Botryosphaeria spp. to pyraclostrobin and highlight the structural characteristics of their cyt b gene. In conclusion, the assessment of Botryosphaeria isolates from various regions in Korea revealed no evidence of resistance to pyraclostrobin so far. However, the risk of resistance of Botryosphaeria populations still exists so it is assumed that continuous monitoring of risk assessment is necessary for Botryosphaeria in Korea.